Bleeding peptic ulcer–risk factors for rebleeding and sequential changes in endoscopic findings. Issue 6 (June 1994) - Hsu, P I; Lin, X Z; Chan, S H; Lin, C Y; Chang, T T; Shin, J S; Hsu, L Y; Yang, C C; Chen, K W
Abstract : From September 1991 to December 1992, a prospective study was conducted to determine the risk factors and residual risk of rebleeding, and the evolutionary endoscopic changes in peptic ulcers that rebled. Emergency endoscopies were performed on 452 patients with haematemesis or a melaena, or both within 24 hours of admission. If the lesions were actively bleeding, then the patients were treated with injection sclerotherapy. A multivariate analysis of clinical, laboratory, and endoscopic variables of 204 patients with ulcer bleeding showed that hypovolaemic shock, a non-bleeding visible vessel, and an adherent clot on the ulcer base were independently significant in predicting rebleeding (p < 0.05). Considering these three factors according to the estimates of their regression coefficients showed that a non-bleeding visible vessel was the strongest predictor of rebleeding. The study of the residual risk of rebleeding after admission showed that most rebleeding episodes (94.1%), including all associated with hypovolaemic shock, surgical treatment, and death, occurred within 96 hours of admission. After this time, the residual risk of rebleeding was less than 1%. Study of the changes in endoscopic findings before and after rebleeding illustrated that all ulcers with a visible vessel or adherent clot showed at follow up endoscopy were derived from ulcers with initial major stigmata. It is concluded that hypovolaemic shock, a non-bleeding visible vessel, and an adherent clot on an ulcer base are of independent significance in predicting rebleeding. Observation for 96 hours is sufficient to detect most rebleeding episodes after an initial bleed from peptic ulcer.